2017
DOI: 10.4236/msa.2017.81007
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation Processes, Regeneration Conditions and Reusability Performance of CaO or MgO Based Catalysts Used for Biodiesel Production—A Review

Abstract: The activity of a catalyst in transestrification reaction usually declines with repeated uses and this limits the possibility to use it many times. This paper presents a review of various techniques used to evaluate the activity changes, the recycling processes for calcium and magnesium oxides based heterogeneous catalysts for biodiesel production. The activity of calcium and magnesium oxides based catalysts declines due to leaching, surface or active sites poisoning by reactant or product molecules and modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 94 publications
(136 reference statements)
2
23
0
1
Order By: Relevance
“…This also agrees well with experiments of continuous operation in CSTR that no significant drop of biodiesel production was observed during startup of the first 10 h. From the beginning of the third circle, the appreciable decreased conversion (more than 11%) was observed, this might be due to the leaching of calcium from CaO‐based catalyst and losing of active basic sites . This also indicates that the consideration of catalyst deactivation must be taken as continuous operation goes on especially after the first 10 h. The reusability of prepared catalyst for transesterification in this work presents a very similar performance with other CaO‐based catalysts for biodiesel production . In this study, since startup stage (first 10 h) is our point of interest, we assume that catalyst deactivation is negligible during the startup period.…”
Section: Resultssupporting
confidence: 90%
“…This also agrees well with experiments of continuous operation in CSTR that no significant drop of biodiesel production was observed during startup of the first 10 h. From the beginning of the third circle, the appreciable decreased conversion (more than 11%) was observed, this might be due to the leaching of calcium from CaO‐based catalyst and losing of active basic sites . This also indicates that the consideration of catalyst deactivation must be taken as continuous operation goes on especially after the first 10 h. The reusability of prepared catalyst for transesterification in this work presents a very similar performance with other CaO‐based catalysts for biodiesel production . In this study, since startup stage (first 10 h) is our point of interest, we assume that catalyst deactivation is negligible during the startup period.…”
Section: Resultssupporting
confidence: 90%
“…Table 2 summarized various mixed and sulphated metal oxides employed as heterogeneous catalysts for biodiesel production. Mixed CaO-MgO had been reported as the most promising catalyst examined [45]. The authors observed that the addition of MgO on CaO and ZnO enhance their activities, but causes formation of soap in the reaction process.…”
Section: Mixed-metal Oxide and Sulphated-metal Oxide Catalystmentioning
confidence: 99%
“…One of the aim using this method is to activate the hydrophilic materials from the moisture or other compounds, such as carbonate ions, that attach on their surface [4].…”
Section: The Role Of Hexane (Washing Agent) and Calcination For Catalmentioning
confidence: 99%
“…The contaminants attach on the catalyst surface, fill the pore, and cover the active sites of the catalyst. Such conditions led to the low accessibility of the active sites of metal oxides to the reactants, which significantly inibit the activity of the catalyst [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation